Analisis Penentuan Sektor Unggulan Perekonomian Wilayah Kabupaten Pasaman - Wenny Widya Wahyudi (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2021)
In realizing economic development, both national development and regional development, one of them can be seen from the perspective of sectoral development, where the sectoral development approach is the achievement of the development target of an area which includes all activities grouped into sectors or business fields. Pasaman District is one of the districts among 12 districts in West Sumatra province. Pasaman District is in the 18th position or the second lowest position at 5 percent. Development in an area should be carried out in sectors which are leading sectors. The leading sector as a driving force for other sectors, therefore the purpose of this study is to determine the leading sectors of the economy in Pasaman District. The analytical method used is the Location Quotient analysis method, Growth Ratio Model, Overlay, and Klassen Typology. From the analysis, it is known that the agricultural, forestry and fisheries sectors are leading sectors that are developed and growing fast but with a low growth rate in Pasaman District.